Cortical response to motor stimulation in neuroleptic-naive first episode schizophrenics - Braus, Dieter F.; Ende, Gabriele; Hubrich-Ungureanu, Petra; Henn, Fritz A. (Psychiatry research, 2000)
The purpose of the present study was to evaluate the cortical response to motor stimulation in neuroleptic-naive first episode schizophrenics in comparison to matched controls using a high speed functional magnetic resonance imaging technique (fMRI). Twelve patients satisfying ICD 10 criteria (F20.0) for schizophrenia (paranoid subtype) as well as sex- and age-matched healthy volunteers participated in this study. All subjects underwent fMRI examination on a conventional 1.5 T MR unit equipped with an echo-planar imaging booster. The blood oxygen level dependent (BOLD) response of the sensorimotor cortex and the higher order SMA region was evaluated during performance of a left hand sequential finger opposition task. Special care was taken to minimize performance and motion artifacts. Patients and controls showed no notable difference with respect to laterality, changes of signal intensity or spatial extent of activation within the primary and higher order motor regions. Using high speed fMRI no fundamental motor cortical dysfunction was evident in a group of paranoid neuroleptic-naive first episode schizophrenic patients. In contrast to data previously reported for chronic disorganized medicated patients, these results suggest that motor dysfunction is not part of the phenomenology of acute paranoid first episode patients.